Comparison of the efficacy of intralesional measles, mumps, and rubella vaccine with intralesional vitamin D3 for the treatment of extragenital warts in pediatric age group (5-18 years) - Jafir Ahmed; Ramesh Kumar Kushwaha; Avinash Sharma; Morish Agarwal; Neha Sharma; Suresh Kumar Jain (Wolters Kluwer Medknow Publications, 2023)
Introduction: Warts are benign skin growths caused by human papillomavirus. Traditional methods of treatment usually include destructive modalities which are painful and scar-forming. Such modalities have disadvantage of recurrence. Consequently, immunotherapy is introduced to overcome these problems. Aims and Objectives: To study the comparative efficacy of intralesional measles, mumps, and rubella (MMR) vaccine with intralesional Vitamin D3 for the treatment of extragenital warts in the pediatric age group (5-18 years). Materials and Methods: Seventy-two immunocompetent patients aged between 5 and 18 years with multiple extragenital warts (2 or more) were enrolled and divided randomly into two groups (Group A and Group B). Group A and Group B received intralesional MMR vaccine and Vitamin D3, respectively, in the largest wart present. The injections were repeated every 2 weeks for a maximum of four injections. Results: Complete response (CR) in injected warts in Group A is seen in 25 (83.3%) patients, partial response (PR) in 3 (10%), and no or inadequate response (NR) in 2 (6.67%) patients. CR is seen in 23 (76.66%) patients of Group B, PR in 4 (13.33%) and no or NR in 3 (10%) patients. CR in distant warts in 22 (73.33%) patients in Group A and 20 (66.66) patients in Group B. Conclusion: Both MMR vaccine and Vitamin D3 are safe, efficacious, and less traumatic to the patients for multiple warts in comparison with destructive modalities.